2003
DOI: 10.1364/ao.42.004080
|View full text |Cite
|
Sign up to set email alerts
|

Native fluorescence and excitation spectroscopic changes in Bacillus subtilis and Staphylococcus aureus bacteria subjected to conditions of starvation

Abstract: Fluorescence emission and excitation spectra were measured over a 7-day period for Bacillus subtilis (Bs), a spore-forming, and Staphylococcus aureus (Sa), a nonspore-forming bacteria subjected to conditions of starvation. Initially, the Bs fluorescence was predominantly due to the amino acid tryptophan. Later, a fluorescence band with an emission peak at 410 nm and excitation peak at 345 m, from dipicolinic acid, appeared. Dipicolinic acid is produced during spore formation and serves as a spectral signature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 33 publications
(31 reference statements)
0
37
0
Order By: Relevance
“…Very few studies on the use of autofluorescence for the detection of bacteria have been reported (2,14). Some bacteria exhibit spontaneous emission spectra following excitation at specific wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies on the use of autofluorescence for the detection of bacteria have been reported (2,14). Some bacteria exhibit spontaneous emission spectra following excitation at specific wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…But this experimental challenge cannot account for the two orders of magnitude differences seen. It has been noted, however, that the procedures used to prepare biological species strongly influence the fluorescence spectra and fluorescence quantum efficiencies -the growth medium, and the number of times the sample has been washed, are known to greatly influence fluorescence profiles; large differences in behavior have also been observed between wet and dry samples; and illumination laser intensities and local concentrations of different fluorophores contained within the biological sample also impact not only the measured fluorescence intensities, but also the wavelength-resolved spectral profiles (Farris et al 1997;Fell et al 1998;Johnson et al 1999;Hill et al 2001;Alimova et al 2003;Kunnil et al 2005;Sarasanandarajah et al 2005b;Atkins et al 2007). …”
Section: Uv Fluorescence Lidarmentioning
confidence: 99%
“…This molecule is prevalent in bacterial spores [17,18] and has been used as a marker molecule in various spectroscopic detection schemes [17,[19][20][21][22]. This molecule is an ideal test molecule for our parameters as it contains the atoms oxygen and nitrogen yet consists of a parent ring structurally similar to benzene, a molecule we have previously investigated with SERID [5,23].…”
Section: Dpa Equilibrium Propertiesmentioning
confidence: 99%